Design of e-learning courseware for hearing impaired (HI) students / Siti Fatimah Saud - Saud, Siti Fatimah (2015)
Nowadays, e-learning courseware will simplify teaching, learning process and give an alternative for teachers to express the information and education for the disable students. The problem is how far the helpfulness of the current education multimedia application can be used suitable and attractive for student disabilities. It is important to note that every student has his or her own individual needs. Therefore, the first objective of this research is to identify specific user requirement for Hearing Impaired (HI) student in their learning. Additionally, second objective is to design the suitable interface of courseware based on the user requirement. This research focuses on design a new interface courseware based on the user requirement of disabilities students mainly for students who have hearing problem. This research was conducted using qualitative methods whereby observation and interview approach was used to collect the data. The data were collected from teachers and students in Sekolah Pendidikan Khas Selangor (SPKS). Besides that, the main contribution of this research is to design the interface of courseware base on the user requirement of hearing impaired student. So, the significance of this application is to increase the attention and intention level for hearing impaired student in their learning process. Thus, the result of this research shows that improvement of design interface based on the user requirement will increase the attention and interest of children to learn.